If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -5p = 30p Solving 6 + -5p = 30p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-30p' to each side of the equation. 6 + -5p + -30p = 30p + -30p Combine like terms: -5p + -30p = -35p 6 + -35p = 30p + -30p Combine like terms: 30p + -30p = 0 6 + -35p = 0 Add '-6' to each side of the equation. 6 + -6 + -35p = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -35p = 0 + -6 -35p = 0 + -6 Combine like terms: 0 + -6 = -6 -35p = -6 Divide each side by '-35'. p = 0.1714285714 Simplifying p = 0.1714285714
| 4(x-3)+3x-14+3(2-4x)=0 | | 3x=y^2-3y+11 | | 7(4s+10)=434 | | y=24*0+45 | | 2n(6)+6=2(4n)+8 | | 21=-4.9x+25x | | p=3*5+8 | | 10x-19=9x+5 | | 12x+12=2x+282 | | 10x-200=3x-11 | | 10x-2=3x-11 | | 6x+31=9x-5 | | 4(4x)+2(x)=70 | | R/8=72 | | 10-x=x+8 | | 9(x+1)-4x=5-(x-3) | | 10x+3=6x-4 | | 4X-5X+8X-7=6X+6X+12 | | f(x)=24ln(x)-0.8x | | 2xy^2+4=2(3-x^2y)dy | | 3x-1+3x=12 | | y=24x+45 | | 2x+1+x+10+x-3=56 | | -3+2x-=3-4x | | 8x-4/2=10 | | tanx=-1.732 | | 1/14÷13/14 | | 9/10÷7/10 | | 2-(7/2y)-(39/4y^2)=0 | | -1x^2+23=0 | | 2x^4p^2-yzq-3z^2=0 | | 4n+25+3n+29=180 |